PEMANFAATAN APLIKASI CANVA SEBAGAI INOVASI PEMBELAJARAN MAHASISWA PGMI PADA MATA KULIAH MEDIA PEMBELAJARAN DI ERA KURIKULUM MERDEKA - Rahmaniah, Neli; Marini, Arita; Azmi, Agus Nilmada (JMIE (Journal of Madrasah Ibtidaiyah Education), 2022)
The Merdeka Curriculum is a curriculum design designed by the government as a strategy in dealing with learning loss due to the co-19 pandemic. The implementation of this independent curriculum strives for the learning process to adjust to the interests and character of students. This is a new challenge for teachers and prospective teachers to innovate in their learning. The teacher must act as a balancer, a link between curriculum goals and the interests and characteristics of students. The existence of a new paradigm shift and an increase in human resources including competent teachers must always be pursued, including by increasing teacher skills to be able to innovate in learning. This study aims to describe the use of the Canva application by educators as a creative, innovative and collaborative learning media in learning in the independent curriculum. This research uses the type of action research (action research). The results of the study after comparing the results of the survey at the beginning and at the end of learning as well as learning outcomes with several cycles, show that the use of the Canva application shows better creative results after being given treatment to PGMI students in making several types of learning media and learning tools such as making posters , infographics, video learning materials, modules, audio-visual media, visual media, presentations, and learning microsites. The results that show changes in creativity are of course very significant as a provision to become basic education teachers who are ready to adapt to the independent curriculum.